Integrating the BSC and KPI Systems for Improving the Efficiency of Logistic Strategy Implementation in Construction Companies - Gryshko, Volodymyr; Zos-Kior, Mykola; Zerniuk, Olena (International Journal of Engineering and Technology, 2018)
The article presents the theoretical and practical basis of BSC and KPI systems integration with a view to improve the efficiency of logistic strategy implementation at construction enterprises. It has been determined that an information logistic system of a construction company should be based on the system of complex performance indexes of logistic activity and it also should have a corresponding to them logistics information system that reflects the running state of logistic strategy implementation and enables to evaluate its efficiency. The exogenous variables, affecting the indicated efficiency, have also been presented in an entry. Based on the research findings, it has been concluded that the proposed guidepost indicators provide an opportunity to insure the process of logistic activity based on modern approaches and procedures in accordance with the chosen logistics strategy of the construction company.Â Â